THE RESULTS OF THE COLONOSCOPIC POLYPECTOMIES - M. Emin CANER; M. Enver DOLAR; K. Bahri ATEŞ; A. Sedat BOYACIOĞLU; Vedia MÜFTÜOĞLU; Nurgül ŞAŞMAZ; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-